Kajian Etnomatika pada Alat Musik Tradisional Bamba di Kecamatan Loura Kabupaten Sumba Barat Daya - Pati, Filigon J. U.; Ghello, Dionisius Lede; Lede, Yulius Keremata (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to identify and describe the ethnomathematical elements found in the bedug, a traditional musical instrument used by the community in Loura Subdistrict, Southwest Sumba Regency. The bedug not only functions as a musical instrument, but also has historical, philosophical, and visual value that reflects the cultural practices of the local community. This study uses a qualitative approach with a descriptive ethnographic research type. Data were collected through direct observation, interviews with traditional leaders and local communities, and documentation of the shape and structure of the bedug. The results show that the bedug contains various mathematical concepts, particularly the concept of spatial geometry, such as circles and cylinders, which are evident in the shape of the base and body of the bedug. These findings indicate that the Sumba community has intuitively applied mathematical principles in cultural practices and the creation of traditional artefacts. This study contributes to the development of ethnomathematics-based mathematics learning by integrating local wisdom, thereby making learning more contextual, relevant, and meaningful for students.